Meta-analysis of Interleukin-6 association with glycated hemoglobin (HbA1c) in pediatric type 1 diabetes mellitus - Lestari, Sally Rizkita; Endaryanto, Anang; Rochmah, Nur; Wungu, Citrawati Dyah Kencono (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Type 1 diabetes mellitus (T1DM) is a chronic illness characterized by the destruction of insulin-secreting pancreatic β-cells. Poor glycemic control in T1DM patients, as reflected by glycated hemoglobin A1c (HbA1c) levels, increases pro-inflammatory cytokine levels, including interleukin-6 (IL-6). This could potentially lead to complications. Research on the correlation between IL-6 and HbA1c levels in children with T1DM has shown conflicting results. Methods: A literature search was conducted on four databases for observational studies investigating the correlation between IL-6 and HbA1c levels in children with T1DM up to June 2024. A random meta-analysis model was performed. Fisher’s r-to-z transformation was applied to standardize effect sizes for each correlation coefficient. Statistical significance was set at p <0.05 for all analyses. Results: This study included 12 observational studies, six of which were cross-sectional. Published between 2003 and 2024, these studies involved 967 children. A pooled correlation coefficient value of 0.29 (95% CI: -0.04 - 0.56) with a p-value of 0.08 was obtained. Conclusions: The correlation between IL-6 and HbA1c levels in children with T1DM showed a trend toward statistical significance. Although not statistically significant, this trend may still be important for understanding the inflammatory processes in T1DM. The weak correlation found between IL-6 and HbA1c levels in these children suggests that elevated pro-inflammatory cytokine concentrations were associated to poor glycemic control.